Egyptian and Other Elements in the Fifth- Century Mosaics of S. Maria Maggiore - Sande, Siri (Acta ad archaeologiam et artium historiam pertinentia, 2017)
The point of departure for this article is the mosaic with Nilotic motifs that runs along the bottom of the apse of S. Maria Maggiore in Rome. The mosaic is a work of Iacopo Torriti dating to 1296. There has been a great deal of discussion, however, whether he invented the motifs or whether he copied them from the fifth-century apse (or even included parts of the original). It is here suggested that Torriti used motifs which were originally present in the fifth-century apse and that they, together with other motifs relating to Egypt in the still preserved fifth-century mosaic panels, had a symbolism well suited to the ideas about Mary and the Incarnation that were prevalent in Rome in the fifth century.